70% Ag 30% Pd Coated BaTiO3 Powder for Internal Electrode Applications. (2002) - Stephenson, R. C.; Peng, Juin-wei
Abstract : Recent trends in the electronic passive component manufacturing industry have been to eliminate or reduce reliance of pure Pd and high palladium contained Ag/Pd electrodes by substituting nickel or significantly lowers palladium content in Ag/Pd alloys. The conversion to base metal technology represents a substantial capital expense; the resistance to replace traditional air-fired kilns to nitrogen or reducing atmosphere kilns has created the need for new low cost air fired electrode technology. This paper presents a new electrode technology incorporating a uniform, continually coated AgPd over engineered dielectric particles. The resulting powder greatly reduces the consumption of precious metal, and provides superior thermal mechanical properties. This is achieved by matching the core ceramic structure of the powder to the manufacturer's dielectric, thereby controlling shrinkage while maintaining desired electrical properties.